PENDEKATAN METODE POHON KEPUTUSAN MENGGUNAKAN ALGORITMA ITERATIVE DICHOTOMIZER (ID3) UNTUK PENGUKURAN KINERJA PEGAWAI NEGERI SIPIL - Yoseph Pius Kurniawan Kelen; Yohanis Ndapa Deda (KH. A. Wahab Hasbullah University, 2016)
Decision tree method is a classification method that has been widely used for the solution of problems of classification. Decision tree classification provides a rapid and effective method. The approach has been proven decision tree method can be applied in various fields of life. Capability classification is indicated by the decision tree method is what encourages authors to use decision tree methods approach to measure the performance of civil servants.Â To build a decision tree induction algorithms used. In this study, the ID3 algorithm method is used to construct a decision tree. Starting with the data collecting training samples and then measuring the entropy and information gain. Information Gain value will be used as the root of a decision tree. And translates it into a decision tree classification rules.The results show that the decision tree method is used to produce classification rules into groups employee performance Good and Bad. The resulting rules are used to measure the performance of employees and classifying employees into two groups.The result to assist management in making more objective assessment process.Â Keywords: ID3 Algorithm, Decision Tree, Employee Performance.